Redescription and placement of the rossellid genus Vazella Gray (Hexactinellida : Lyssacinosida) - Reiswig, H.M. (Bulletin de l'Institut royal des Sciences naturelles de Belgique, 1996)
Two hexactinellid sponges from the Florida Keys, Holtenia pourtalesii and H. saccus, described by O. Schmidt in 1870, were re-examined to determine their taxonomic status. Both belong to a single species which is redescribed here. The species belongs to the subfamily Rossellinae (Hexasterophora, Lyssacinosida) but cannot be included in any of the recognized genera. The genus Vazella, Gray, 1870, is reinstated to accommodate the single species, Vazella pourtalesi (Schmidt, 1870).